Stigma and its influencing factors among breast cancer survivors in China: A cross-sectional study - Jin, Ruiqi; Xie, Tingting; Zhang, Lijuan; Gong, Ni; Zhang, June (European journal of oncology nursing : the official journal of European Oncology Nursing Society, 2021)
Although stigma has attracted considerable scholarly attention, few studies have focused on its influencing factors among discharged breast cancer survivors, especially in a Chinese cultural context. The present study therefore explores stigma and its influencing factors among breast cancer survivors in China. Between December 2017 and May 2018, 103 breast cancer survivors at the outpatient clinic of a tertiary cancer center in southern China were enrolled in a cross-sectional study. The research instruments comprised the Social Impact Scale (SIS), the General Self-Efficacy Scale (GSES), the Medical Coping Modes Questionnaire (MCMQ), and sociodemographic and disease-related questionnaires. Descriptive statistics, univariate analysis, and multivariable linear regression were used to explore the current status of stigma and to identify influencing factors. Of the respondents, 76.7% and 8.7%, respectively, reported moderate and high levels of stigma. The mean SIS score was 55.20 ± 12.15 (moderate), and the SIS subscale with the highest average score was financial insecurity. The results of a multivariable linear regression showed that body image (β = 0.32, P＜0.001), spousal support (β = −0.47, P < 0.001), personal acceptance of the disease (β = −0.22, P＜0.001), coping modes (resignation) (β = 0.14, P < 0.001), support from medical staff (β = −0.23, P < 0.001) and self-efficacy (β = −0.10, P = 0.037) were the main factors influencing stigma among breast cancer survivors (R2 = 0.83). Stigma, among breast cancer survivors, which is influenced by various sociocultural factors, is a neglected issue requiring attention. Healthcare professionals should therefore formulate effective measures for alleviating stigma in this group by improving their self-efficacy and acceptance of the disease, reducing their poor body image and negative coping mode, and eliciting more support from their spouses and medical staff. •In Chinese culture, breast cancer survivors experience stigmatization due to negative personalities, bad feng shui or karma.•Chinese breast cancer survivors experienced more severe economic insecurity.•Stigma persists in the diagnosis, treatment and recovery period, which should be valued by healthcare professionals.•Self-efficacy, personal acceptance of the disease and perceived social support have a negative influence on stigma.•Poor body image and resignation-based coping has a positive influence on stigma.